2009
DOI: 10.1016/j.appet.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between needs driving eating occasions and eating behavior in midlife women

Abstract: The purpose of this cross-sectional study was to determine the relationship between type of eating occasion based on need state segments experienced by 200 midlife women (46 ± 6 years) and food group, nutrient, and energy intake. Women completed an Eating Occasion Questionnaire for 3 eating occasions over a 3-day period for which they maintained diet records. Cluster analysis segmented 559 eating occasions into six need states. Energy, total fat, and cholesterol consumption per occasion were highest in "routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Men tended to maintain the same diet throughout their lives. Women though were more likely to dictate food choices from the store and therefore also dictate food choices for meals because they "control" what comes into the house [34,35]. So even though women are more willing to compromise on meals eaten, they will determine ingredients and specific brands into each meal, creating a way to add their own standards within the meal.…”
Section: Life Coursementioning
confidence: 99%
“…Men tended to maintain the same diet throughout their lives. Women though were more likely to dictate food choices from the store and therefore also dictate food choices for meals because they "control" what comes into the house [34,35]. So even though women are more willing to compromise on meals eaten, they will determine ingredients and specific brands into each meal, creating a way to add their own standards within the meal.…”
Section: Life Coursementioning
confidence: 99%
“…Researchers have divided consumers into groups based on shared characteristics [ 19 , 20 ], that affect food intake behaviors. Another less common but potentially useful approach is to categorize eating occasions (meals and snacks), as tested in a feasibility study among midlife women [ 21 ]. Results from this study showed that the type of need addressed within an eating occasion affected food and nutrient intakes among midlife women.…”
Section: Introductionmentioning
confidence: 99%